2012
DOI: 10.1007/s11434-012-5341-6
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cd(II) from acidic aqueous solutions by tourmaline as a novel material

Abstract: Batch experiments were conducted to investigate the behavior and mechanisms for the adsorption of Cd(II) from aqueous solutions by tourmaline under acidic conditions. The results indicated that the adsorption of Cd(II) significantly depend on the adsorption time, temperature, and the initial concentration of the metal ion. Furthermore, tourmaline had a very good adsorption capacity for Cd(II) in acidic, neutral and alkaline aqueous solutions. This good adsorption capacity is attributed to the observation that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…Hence, the effect of pH on Cd 2+ adsorption onto NC can be described by an electrostatic attraction mechanism between NC and charged sorbent surfaces. Corresponding to the electrostatic interaction force, for cationic Cd 2+ , the adsorption quantity reduced with decreasing pH value owing to electrostatic repulsion force. , It is interesting to mention that further obtained information from isotherms will approve this proposition.…”
Section: Resultsmentioning
confidence: 87%
“…Hence, the effect of pH on Cd 2+ adsorption onto NC can be described by an electrostatic attraction mechanism between NC and charged sorbent surfaces. Corresponding to the electrostatic interaction force, for cationic Cd 2+ , the adsorption quantity reduced with decreasing pH value owing to electrostatic repulsion force. , It is interesting to mention that further obtained information from isotherms will approve this proposition.…”
Section: Resultsmentioning
confidence: 87%
“…A significant contribution to the employment of tourmaline for extraction of heavy metals from aqueous solution has been made by Wang’s team. Tourmaline (0.5–50 and 60–180 μm particle sizes) from Xinjiang, China was selected. They found that cathode of tourmaline could adsorb heavy metals and scattered needle or rod-shaped crystals were observed on the surface of tourmaline of 0.5–50 μm after adsorption, which did not appear in tourmaline of 60–180 μm (Figure ).…”
Section: Adsorption Of Heavy Metals On Diatomite-based Functional Mat...mentioning
confidence: 99%
“…The band at 1740-1480 cm −1 is assigned to the stretching vibrations of C=O in carboxylic acids, anhydrides, lactones, esters, carboxylic salts, carboxylo-carbonates, quinones, and hydroxyquinones [13,14], and C=C in carboxylic or pyridine-like structure [15]. A intense band at about 1300-1000 cm −1 corresponds to the stretching in C-O, C-O-C, O-H in carboxylic acids, anhydrides, lactones, esters, ethers, phenols, epoxides and carboxyl-carbonates, which are also overlapped [11][12][13][14][15][16].…”
Section: Ftir and Boehm Titration Datamentioning
confidence: 97%